STRUKTUR SOSIAL MASYARAKAT NELAYAN KOTA BENGKULU : Kajian Struktural Tentang Kemiskinan Nelayan Kota Be gkulu (Social Structure of Fisherman Community at Bengkulu City)1 - Apriyanty, Henny; S. Alikodra, Hadi; M, Kooswardono; Sutarto, Endriatmo; Kolopaking, Lala M (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2006)
Fisherman community in Bengkulu city which divided into groups based on ethnic and authority of production asset. Sumberjaya district is the modern area fishery, the profit sharing system indicates the large imbalance relatively in distribution which cause distribution not covered all out relatively in eaming distribution. And in Teluk Sepang district which is fishery area, the profit sharing system indicates small imbalance relatively, even still cause distribution which not covered all out. The tightly relationship client patron has seen clearly in Sumberjaya district which make high dependance relatively between owner of production equipment with laborer of ship fisherm8n, hence pONerty will keep existing, while in Teluk Sepang district has not seen the patron client relationship, however the pONerty still existing because of the limited production tool. Marketing distribution of fish based on kind of fisherman exertion. FIsherman exertion which using ·purseine